(untitled) (La U Investiga, 2018)
The objetive was to describe the degree of knowledge, understanding and use of the nutritional traffic light (NTL) in consumers of the main supermarket chains, Ibarra, Ecuador. The research was quantitative-qualitative. A structured interview was used in large supermarkets. Ibarra, Ecuador; also, the ethnographic observation: and the Focus Groups with Consumers. The results showed thatn77.1% of interviewees said they know the nutritional traffic light. Of those people who know him 98% could give a correct description of it and 98.1% consider the NTL to be mandatory or very important and 65.7% agree on the NTL’s usefulness at the time of making the purchase considering it very important, despite this, only 23% always consult, The reason why the traffic light is consulted is to choose healthier foods (55.1%); NTL consultation influences the choice of the type of drinks and the type of food by the consumer. In general, participants in the focus group recognize that the NTL shows information on the content of fats, sugar and salt contained in food. The answers given when asked the reasons why they review the NTL, are consistent with the knowledge expressed. On the suggestions to improve the use, the answers agree in diminishing the consumption of foods with high content of fats, sugars and salt. It is concluded that a high percentage of respondents shows knowledge and understanding of the SN, is interested in reviewing it before buying a processed food, however, only half of them use it for prevention or treatment of diseases related to malnutrition or for reduce the consumption of sugars, fats and salt.